FAKTOR-FAKTOR YANG MEMENGARUHI REMUNERASI DIREKSI: STUDI KOMPARASI PERUSAHAAN DI AUSTRALIA, SINGAPURA, INDONESIA, DAN MALAYSIA - Probohudono, Agung Nur; Perwitasari, Dwi; Putra, Rifky Pratama (Jurnal Akuntansi dan Keuangan Indonesia, 2016)
The purpose of this paper is to analyze factors affecting directors’ remuneration. Factors tested in this study are distress status, company performance, ownership structure and board composition. Sample of this study is non-financial companies listed in Indonesia Stock Exchange, Malaysia Stock Exchange, Singapore Stock Exchange and Australian Stock Exchange. A total of 474 companies’ financial reports are used in this study for the period of 2011-2013. This study uses purposive sampling method to select the sample. This study uses multiple regression to examine factors that affect directors’ remuneration. The result shows that average of directors’ remuneration for distress and non-distress companies in Indonesia, Malaysia, Singapore and Australia is different. Singaporean firms tend to provide higher directors’ remuneration than other countries, while the lowest ones are Malaysian firms. The result shows that distress status, managerial ownership and ownership concentration affect directors’ remuneration, while the shareholder return, ROA and board composition do not affect the directors’ remuneration. This paper is beneficial to connect between remuneration and corporate performance when firms experience distressed and non-distressed. This paper also provides contribution for firms, investors and practitioners in issue related to directors’ remuneration.